Imperata cylindrica root as PGPR pressing the pathogen phytophthora infestant the cause of wilt disease in potato plant (Solanum tuberosum L.) - Roeswitawati Dyah; Sutarman Sutarman; Indratmi Dian (BIO Web of Conferences)
Potatoes (Solanum tuberosum L.) are a staple food worldwide, in addition to wheat, corn, rice, and wheat. In Indonesia, the potato commodity has received priority for development because it is a source of non-rice carbohydrates and has the potential for food diversification programs. Since 2016, Indonesian potato production has decreased due to attacks by the fungus Phytophthora infestans. Potato plants attacked by Phytophthora infestans show symptoms in small wet spots coloured pale green to dark green. So far, potato farmers have only relied on chemical pesticides to control these pathogens. The research aimed to test the potential of the Imperata cylindrica root to suppress the Phytophthora infestans pathogen that causes potato disease (Solanum tuberosum L.). The results show that the Imperata cylindrica root as PGPR can reduce the intensity of Phytophthora infestans attacks on potato. This is not significantly different compared to factory-made PGPR (Biopharma) but is significantly different compared to PGPR, which comes from the roots of bamboo plants. It is suspected that in the rhizosphere of the plant there are bacteria that release secondary metabolites so that they can suppress the Phythtopthora infestant pathogen through the process of antibiosis.